Politics of scale in environmental struggles: the case of the wetlands in Argentina (Huellas, 2021)
Struggles over the use and appropriation of the environment are one of the main objects of study of Political Ecology. The aim of this article is to analyze the struggles over the production of public policies that prescribe the forms of use and appropriation of the environment in the wetlands ecosystems in Argentina, between 2008 and 2019. In order to achieve this aim, we activate the concept ‘politics of scale’ coined by Neil Smith, who interprets scale as an instrument for political struggle. Through the use of a historical-narrative strategy, we reflect on the produced character of the scale in the processes under analysis and observe the changes that have occurred over time, as a result of dynamic social relations between multiple actors. Throughout the analysis, we identify several actions deployed by social actors to promote or restrict the creation of public policies aimed at regulating productive activities in the wetlands ecosystems and at favoring their protection. We conclude that a political ecology of scale may be constituted not only as an analytic tool for understanding environmental struggles, but also as a political tool capable of promoting new scalar arrangements that favor emancipatory policies.
Keywords: politics of scale; environmental laws; wetlands; Wetlands Law